(untitled) (Indian Journal of Public Health Research & Development, 2020)
Background: Globally as of 2013, an estimated 382 million people or 8.3% of adults, are estimated to have diabetes, out of which about 46% were undiagnosed. The disease affects more than 50 million Indians-7.1% of the nation adults and kills about 1 million Indians a Year. The prevalence in south India has been reported to vary between 0.7% in Pondicherry to 19.5% in Kochi in urban areas. Objectives: 1. To find out the prevalence of type 2 diabetes mellitus among adults in urban population of Eluru. 2. To study the socio-demographic variables in relation to type 2 diabetes mellitus in the study population. Methodology: This was a community based cross sectional study carried out in the urban area of Eluru for a period of one year among 454 adults 30 years and above age group. WHO diagnostic criteria was used. The data was collected using a pretested semi structured questionnaire. All data collected was entered and analysis was done by using the Microsoft Office Excel 2007 and necessary statistical tests like proportions and chi square tests were applied. Results: In the present study 48.9 percent of the study population were males and 51.1 percent were females. The prevalence of the type 2 diabetes mellitus was 21.1 percent in the present study. The present study showed significant association between the educational status and diabetes mellitus (p<0.0001). Statistical significant association (p<0.05) was found between different socio economic class of people and Diabetes mellitus. Conclusion: Prevalence of type 2 diabetes mellitus in the urban population was showing increasing trend. Diabetics and high-risk groups should be included in the health education, IEC activities and counseling programmes.